1976
DOI: 10.1111/j.1445-2197.1976.tb03328.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Povodone Iodine Solution in the Prevention of Wound Sepsis

Abstract: In a prospective blind trial in patients undergoing intraabdominal surgery, instillation of povodone iodine (PVI) solution into the wound failed to reduce the incidence of wound sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…[19][20][21][22] Some investigators reported the benefits of colonic irrigation with PVI on reducing wound infection rate. 23,24 However, the unprepared group also showed a lower wound infection rate than those with preparation.…”
Section: Wound Irrigationmentioning
confidence: 99%
“…[19][20][21][22] Some investigators reported the benefits of colonic irrigation with PVI on reducing wound infection rate. 23,24 However, the unprepared group also showed a lower wound infection rate than those with preparation.…”
Section: Wound Irrigationmentioning
confidence: 99%
“…The studies compared PVI irrigation or spray of subcutaneous tissues following fascial closure to a control group. Two of the studies used PVI-based spray [14, 15], while the 3 others used variations of PVI solution [12, 13, 16]. The control groups either received no treatment [12, 14, 15] or irrigation of subcutaneous tissues with normal saline [13] or iodine tincture to skin edges [16].…”
Section: Resultsmentioning
confidence: 99%
“…4, 5). In both studies [12, 15] the surgeon was made aware of assignment of the patient following closure of the peritoneum. The other 3 studies provided no clear description of the concealment from the treating surgeon [13, 14, 16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations